2021
DOI: 10.1080/21655979.2021.1940042
|View full text |Cite
|
Sign up to set email alerts
|

Cullin-5 (CUL5) as a potential prognostic marker in a pan-cancer analysis of human tumors

Abstract: There is some evidence supporting an association between Cullin-5 (CUL5) and cancer, but no research using pan-cancer analysis has been conducted previously. We therefore investigated the oncogenic role of CUL5 in 33 tumors from the Gene Expression Omnibus and The Cancer Genome Atlas databases. Many cancers reduce CUL5 levels, and the prognosis of certain cancers is vitally linked with CUL5 expression. CUL5 expression is associated with CD8 + T-cell infiltration levels in uveal melanomas and head and neck squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Knockdown of RBX1 has also been correlated with decreases in the growth of HCC xenografts and the induction of cell cycle arrest and senescence in HCC cells ( Yang et al, 2013 ). RBX1, ELOB, and ELOC can also interact with CUL5 and WSB1, both of which are overexpressed in HCC, to form the CRL5 WSB1 complex ( Okumura et al, 2012 ; Xu et al, 2020 ; Li et al, 2021 ). This E3 ligase complex has a number of targets, including HIPK2, whose loss downregulates apoptosis, and pVHL ( Okumura et al, 2012 ; Kim et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of RBX1 has also been correlated with decreases in the growth of HCC xenografts and the induction of cell cycle arrest and senescence in HCC cells ( Yang et al, 2013 ). RBX1, ELOB, and ELOC can also interact with CUL5 and WSB1, both of which are overexpressed in HCC, to form the CRL5 WSB1 complex ( Okumura et al, 2012 ; Xu et al, 2020 ; Li et al, 2021 ). This E3 ligase complex has a number of targets, including HIPK2, whose loss downregulates apoptosis, and pVHL ( Okumura et al, 2012 ; Kim et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…We visited the functional protein association networks’ (STRING) web server ( https://string-db.org/ ) ( Szklarczyk et al, 2015 ) with the basic parameters defined as follows: minimum required interaction score (“low confidence 0.150”), maximum number of interactors to display (“no more than 50 interactors” in the first shell), meaning of the network edges (“evidence”), and active interaction sources (“experiments”), as previously stated ( Li et al, 2021 ). Finally, we acquired the top 50 KDM6B-related proteins with experimental evidence.…”
Section: Methodsmentioning
confidence: 99%
“…An ATP-driven chaperone cycle controlled by various cochaperones is required for the HSP90-mediated activation and stability of customer proteins. This is accomplished via an ATP-driven chaperone cycle . The deprivation of HSP90 mediated by Cul5 is not based on the function of either the elongin B or C as indicated by directing elongin C, which can fix Cul5 but not the SOCS box inside substrate receptors that affect ErbB2 denaturation .…”
Section: Some Common Substrates Of Cul5mentioning
confidence: 99%
“…Xu and his team have shown that the neddylation and ubiquitination complexes of UBE2F–Cul5–RBX2 and UBE2M–Parkin/DJ-1 enzymes regulate apoptosis from NOXA turnover . First, UBE2F, one of two neddylators of the ubiquitin-conjugated enzyme (E2), collaborates with RBX2 serving as the E3 neddylator, which initiates Cul5 neddylation around the triplet of a lysine residue (Lys724) . Cul5 activity depends on the presence of this enzyme.…”
Section: Some Common Substrates Of Cul5mentioning
confidence: 99%
See 1 more Smart Citation